EU:s inflytande vid gränskonflikter: Fallet Cypern- En fallstudie av EU:s maktutövning i Cypernkonflikten - Sivén,Christa (2007)
This study discusses the European Union´s influence regarding the Cyprus Conflict since 1998, when the EU began the official membership negotioations with Cyprus. The first aim of the study is to investigate in what way the EU has tried to practice influence concerning the Greek- and Turk Cypriots, but also Turkey, since Turkey is seen as a relevant party in the conflict. The second aim of the study is to examine what effects the EU´s influence has led to for the parties involved. The theoretical approach in the study is the theory Normative power, the theory stresses that Europe and the EU practices non-military power, and is able to do so because of the fact that the EU is based on internationally acknowledged desirable norms, as democracy and human rights and liberties. The result of the study shows that the EU has been an active participant concerning the Cyprus Conflict by successfully influencing the Greek- Cypriot government and Turkey e.g. Another noticeable result that is shown is that the EU has failed to influence the Turk- Cypriot leadership and that the union also repeatedly has misjudged the situation and the actions of both the Greek- and Turk Cypriot communities.
Keywords: Cypern; Cypernkonflikten; EU; EU-inflytande; Normative power; Political and administrative sciences; Statsvetenskap, förvaltningskunskap